2000
DOI: 10.1007/s0028400
|View full text |Cite
|
Sign up to set email alerts
|

Waste Water Bacterial Isolates Resistant to Heavy Metals and Antibiotics

Abstract: Sewage water of Casablanca, an industrial city in Morocco, was studied for microorganisms resistant to heavy metals. Isolates were purified and collected on agar slants to be screened for resistance to heavy metals, including mercury in vitro. The strains that showed high resistance to heavy metals were also studied for their resistance to antibiotics and aromatic hydrocarbons. Results indicated that the strains most resistant to all tested products belonged to Ps. fluorescens, Ps. aeruginosa, Klebsiella pneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(32 citation statements)
references
References 8 publications
3
29
0
Order By: Relevance
“…Hospital effluents are a major source of environmental contamination and contribute substantially to changes in the Pseudomonas communities. Our metagenomic data is therefore in agreement with previous studies that have shown that hospital wastewater discharges can change the structure and composition of the bacterial communities that they are discharged into [16, 2630].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…Hospital effluents are a major source of environmental contamination and contribute substantially to changes in the Pseudomonas communities. Our metagenomic data is therefore in agreement with previous studies that have shown that hospital wastewater discharges can change the structure and composition of the bacterial communities that they are discharged into [16, 2630].
Fig.
…”
Section: Resultssupporting
confidence: 92%
“…The results indicate that P. aeruginosa shows resistance compared to other bacteria as reported by Rachid (181) Tables I and II. The results indicate that these strains show resistance compared to other bacteria, as reported by Filali et al [11]. Strain P-7 was found to be the most resistant strain to the metals and antibiotics.…”
Section: Minimal Inhibitory Concentration Of Metal and Antibioticssupporting
confidence: 77%
“…and P. mirabilis strains, highly tolerant especially to copper and also to chromium, cobalt, cadmium, zinc, and mercury. Also, a highly resistant to several heavy metals (including mercury, copper, zinc, cadmium, cobalt, silver, and others) P. mirabilis strain was identified in wastewater samples from Casablanca City, Moroccco, also exhibiting resistance to naphthalene, anthracene, and antibiotics [40]. Another strongly copper resistant strain identified as P. vulgaris and isolated from soil samples collected near the Panki power plant in Kampur, India, was reported by Rani et al .…”
Section: Proteus In Bioremediation and Plant Growth Promotionmentioning
confidence: 99%